2022
DOI: 10.1002/pd.6225
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐assisted fetal laser surgery in the treatment of twin‐to‐twin transfusion syndrome: Recent trends and prospects

Abstract: Fetal laser surgery has emerged as the preferred treatment of twin-to-twin transfusion syndrome (TTTS). However, the limited field of view of the fetoscope and the complexity of the procedure make the treatment challenging. Therefore, preoperative planning and intraoperative guidance solutions have been proposed to cope with these challenges. This review uncovers the literature on computerassisted software solutions focused on TTTS. These solutions are classified by the pre-or intraoperative phase of the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…On the other hand, smaller cannula diameter decreases the field of view and increases the risk of incomplete surgery, which also negatively affects pregnancy outcome 24 . To overcome both considerations, attempts have been made to artificially expand the field of view during fetoscopy using computer‐assisted interventions 30 . In addition, several studies have identified possible factors in surgical techniques to improve PPROM rates after fetal laser surgery, like using the Seldinger technique during fetoscopic port insertion, a chorioamnion plug, or sealing the membranes 28 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, smaller cannula diameter decreases the field of view and increases the risk of incomplete surgery, which also negatively affects pregnancy outcome 24 . To overcome both considerations, attempts have been made to artificially expand the field of view during fetoscopy using computer‐assisted interventions 30 . In addition, several studies have identified possible factors in surgical techniques to improve PPROM rates after fetal laser surgery, like using the Seldinger technique during fetoscopic port insertion, a chorioamnion plug, or sealing the membranes 28 …”
Section: Discussionmentioning
confidence: 99%
“…The fetoscopic laser procedure is challenging, mainly due to the fetoscope's limited field of view, leading to increased procedural time and incomplete ablation of anastomoses. Computer-assisted technologies, like placental vessel segmentation and fetoscopic image stitching algorithms for the fetal environment, have been developed to overcome the limited field of view challenges by supporting the identification of the placental vessels and anastomoses [2].…”
Section: Introductionmentioning
confidence: 99%